How Could a Social Network Analysis Boost an Evolutionary Ecosystem in Cultural Heritage Tourism? - Darko Dimitrovski; Arja Lemmetyinen; Lenita Nieminen (Finland, 2025)
Cultural heritage has become a valuable resource from which the themes and narratives essential to ‘place-making’ can be derived by tying the physical assets, for example, buildings, and the living culture together. In this research note we present our research proposal answering the following research question: How could a social network analysis (SNA) boost an evolutionary ecosystem in cultural heritage tourism? In a longitudinal case study, we will identify the current formal and informal ties of the stakeholders making it possible to assess their cohesiveness and predict the future success of an ecosystem. Research using a combination of a SNA and interactive network theories is scarce thus justifying our study. The practical implications of the study are perceived to be significant.
Proceedings of the Heritage, Tourism and Hospitality International Conference HTHIC 2017 September 27-29, 2017 Pori, Finland